MANAJEMEN KINERJA KEUANGAN USAHA KECIL DAN MENENGAH DI SUMATERA SELATAN - Diana Widhi Rachmawati; Yudhistira .; Nisrina .; Nur Agung Dinarto (Fakultas Ekonomi Universitas Tridinanti Palembang, 2018)
Economic development will meet the needs of human beings today that are not comparable with the level of employment, which eventually led to the creation of jobs in the form of small and medium enterprises. Many of the business fields that are created today are sales from directly to consumers and using technology, they are small and medium enterprises, namely the Gas Base business, Mount Dempo Coffee Powder and Basic Food Stores. Management of Financial Statement Analysis is an art of application tools and analysis techniques for general purpose financial statements and related data to produce estimates and conclusions that are useful in business analysis. Financial Report Analysis used in this study uses the ratio analysis method.The general objective is to provide information on the development of financial performance of small and medium enterprises in 2016 seen from the ratio analysis. Samples from this study were: Gas Base, Mount Dempo Coffee Powder and Basic Food Stores.The results of the research achieved are in general the Base Gas, Gunung Dempo Coffee Powder and the Basic Food Stores in South Sumatra are still in the process of developing. Because there are still many of the above ratios that have not been as expected, such as not yet lavarage or solvabel and still need to pursue the achievement of profit. Keywords: Small and Medium Business Financial Performance Management